The associations between public stigma and support for others’ help-seeking for alcohol use disorder: a cross sectional study in the general Danish population - Sara Wallhed Finn; Anna Mejldal; Anette Søgaard Nielsen (Addiction Science & Clinical Practice, 2023)
Abstract Background A minority of all individuals with alcohol use disorders (AUD) seek treatment, where stigma is one prominent barrier. Social support is important to facilitate health and increase treatment-seeking. Whether there is an association between stigma and attitudes towards others’ help-seeking for AUD is unknown. The aim of this study was to investigate the associations between stigma and support towards others’ help-seeking for AUD, also to explore possible gender differences. Method Cross-sectional study, n = 2895, including Danish adults aged 30–65 in the general population. Year 2020, an online questionnaire was administrated, which covered demographics, attitudes towards others’ help-seeking for AUD, and stigma measured with the Difference, Disdain & Blame Scales. Analyses were performed with Restricted Cubic Spline models, and odds ratios were calculated. Results Lower level of stigma was associated with a higher probability for endorsing an “active support strategy”. Level of stigma was not associated with “not knowing what to say or do” or “sharing my concern with others”. There were few gender differences: among men, higher level of stigma was associated with a higher probability of “avoidance”. Among women, lower level of stigma was associated with a lower probability of “avoidance”. Conclusion There is a clear association between stigma and attitudes towards supporting others’ help-seeking for AUD. The results highlight the need to reduce stigma and promote engagement towards others’ treatment-seeking.